A Curriculum in Vocational Courses: The Recognition and (Re)Construction of Counterhegemonic Knowledge. Issue 3 (3rd July 2019) - Marinho, Paulo; Delgado, Fátima
Abstract: This article highlights the construction of practiced curriculum in vocational courses, stemming from networks of knowledge woven into curricular (re)contextualization and supported by the diversity of everyday knowledge of young students. The experience of this curriculum has allowed the recognition and (re)construction of counterhegemonic knowledge that has produced greater academic success and empowerment of all students—encouraging autonomy, motivation, and active participation—in the constructive process of learning.